Synthesis and Characterization of Bipolar Hosts Based on Triphenylamine and 4,5- Diazafluorene Through Friedel-Crafts Reaction - Li, Nengquan; Chen, Kun; Fan, Zhaokang; Quan, Yiwu; Chen, Qingmin (Current Organic Synthesis, 2015)
A new family of bipolar hosts TPA-DAF, TPA-(DAF)2 and TPA-(DAF)3 based on triphenylamine and 4,5- diazafluorene moiety were synthesized through Friedel-Crafts reaction, and all of the three prepared hosts showed excellent thermal stability and exhibited blue fluorescence in solution.
Keywords: nonplanar configuration